Modulating the Infarcted Ventricle'S Refractoriness with An Epicardial Biomaterial. (February 2021) - Chinyere, Ikeotunye Royal; Hutchinson, Mathew; Moukabary, Talal; Koevary, Jen Watson; Juneman, Elizabeth; Goldman, Steven; Lancaster, Jordan J
Patients diagnosed with heart failure with reduced ejection fraction (HFrEF) are at increased risk of monomorphic ventricular tachycardia (VT) and ventricular fibrillation. The presence of myocardial fibrosis provides both anatomical and functional barriers that promote arrhythmias in these patients. Propagation of VT in a reentrant circuit depends on the presence of excitable myocardium and the refractoriness of the circuit. We hypothesize that myocardial refractoriness can be modulated surgically in a model of HFrEF, leading to decreased susceptibility to VT. Male Sprague-Dawley rats were infarcted via permanent left coronary artery ligation. At 3 weeks post-infarction, engineered grafts composed of human dermal fibroblasts cultured into a polyglactin-910 biomaterial were implanted onto the epicardium to cover the area of infarction. Three weeks post-graft treatment, all rats underwent a terminal electrophysiologic study to compare monophasic action potential electroanatomic maps and susceptibility to inducible monomorphic VT. HFrEF rats (n=29) demonstrated a longer (p=0.0191) ventricular effective refractory period (ERP) and a greater (p=0.0394) VT inducibility compared with sham (n=7). HFrEF rats treated with the graft (n=12) exhibited no change in capture threshold (p=0.3220), but had a longer ventricular ERP (p=0.0029) compared with HFrEF. No statistically significant change in VT incidence was found between HFrEF rats treated with the graft and untreated HFrEF rats (p=0.0834). Surgical deployment of a fibroblast-containing biomaterial in a rodent ischemic cardiomyopathy model prolonged ventricular ERP as measured by programmed electrical stimulation. This hypothesis-generating study warrants additional studies to further characterize the antiarrhythmic or proarrhythmic effects of this novel surgical therapy.